Portuguese Parenting Styles, Adolescents´ Personal Competence and Internalization of Values - Rodrigues, Yara (2015)
This chapter analyzes current evidence between parenting styles and adolescent outcomes for the Portuguese context. Parenting styles and adolescent outcomes were analyzed in a sample of 517 Portuguese adolescents aged 11 to 19 years old, of whom 214 (41.4%) were males. The adolescents were classified into 1 of 4 groups (authoritative, authoritarian, indulgent, and neglectful) on the basis of self reported ratings of their parents on two dimensions: Acceptance/involvement and strictness/imposition. Adolescents were contrasted along two different set of outcomes: (1) priority given to Schwartz's values (self-direction, universalism, benevolence, tradition, conformity, security and realization) and (2) level of Self-esteem (appraised in five domains: academic, social, emotional, family, and physical). Regarding the consequences of using a particular parenting style on the personal and social adjustment of children, studies from Anglo-Saxon literature suggest that the children from authoritative families display a better adaptation that children socialized with other parenting styles. Results with Portuguese adolescents suggest that adolescents from indulgent families score the same, and even better than those of authoritative families, in some indicators of psychosocial adjustment. The study refers to the need for further research, taking into account new contexts and new cultures.